GAMBARAN HISTOPATOLOGI PARU PADA MENCIT (Mus musculus) YANG DIPAPAR ASAP ROKOK KRETEK AKIBAT PENGARUH PEMBERIAN INFUSA TEH HIJAU (Camellia sinensis) - Dyah Widhowati; Rondius Solfaine; Olan Rahayu Puji Astuti Mussa; Apriska Ayuningtias (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
This study was conducted to determine the effect of antioxidant administration from green tea infusion (Camellia sinensis) on damage to the histological structure of the lung exposed to clove cigarette smoke in mice (Mus muscullus). Free radicals in cigarette smoke such as tar, nicotine, and carbon monoxide can cause various damages to the lung or This study was conducted to determine the effect of antioxidant administration from green tea infusion (Camellia sinensis) on damage to the histological structure of the lung exposed to clove cigarette smoke in mice (Mus muscullus). Free radicals in cigarette smoke such as tar, nicotine, and carbon monoxide can cause various damages to the lung organs due to oxidative stress caused by the reaction of ultrafine particles with cells. A total of 27 mice were taken from the Biochemical Laboratory of Airlangga University, Surabaya. In this study mice (Mus muscullus) were exposed to kretek cigarette smoke in the smoking chamber for 15 minutes in a period of 2 weeks, used 2 variants of antioxidant doses of green tea infusion of 0.45 gr to 0.6 gr. After the treatment was completed, the preparation of the mice's pulmonary organ preparations and damage to the structure of the lung organ were observed in 9 visual fields. The results showed that there was a relationship between the amount of cigarette smoke exposed and damage to the lung organs of mice when given antioxidant green tea. The administration of green tea antioxidants reduced inflammation of the lung organ infiltration of inflammatory cells by 44%, edema by 55%, and destruction of septa alveoli by 88%. gans due to oxidative stress caused by the reaction of ultrafine particles with cells. A total of 27 mice were taken from the Biochemical Laboratory of Airlangga University, Surabaya. In this study mice (Mus muscullus) were exposed to kretek cigarette smoke in the smoking chamber for 15 minutes in a period of 2 weeks, used 2 variants of antioxidant doses of green tea infusion of 0.45 gr to 0.6 gr. After the treatment was completed, the preparation of the mice's pulmonary organ preparations and damage to the structure of the lung organ were observed in 9 visual fields. The results showed that there was a relationship between the amount of cigarette smoke exposed and damage to the lung organs of mice when given antioxidant green tea. The administration of green tea antioxidants reduced inflammation of the lung organ infiltration of inflammatory cells by 44%, edema by 55%, and destruction of septa alveoli by 88%.